Evidence of Rectal Carcinoma in the Background of Solitary Rectal Ulcer Syndrome with Pathological Complete Response after Preoperative Radiotherapy: A Case Report and Narrative Review of Literature - Yasir Ahmad; Rashidah Mohamad Khalid; Razrim Rahim (Surgical Society Of Northern Greece, 2024)
Volume 28, issue 1